Glucose-oxygen deprivation constrains HMGCR function and Rac1 prenylation and activates the NLRP3 inflammasome in human monocytes - Raulien, Nora; Friedrich, Kathleen; Strobel, Sarah; Raps, Stefanie; Hecker, Friederike; Pierer, Matthias; Schilling, Erik; Lainka, Elke; Kallinich, Tilmann; Baumann, Sven; Fritz-Wallace, Katarina; Rolle-Kampczyk, Ulrike; et al. (Science Signaling, 2024)
Hypoxia and low glucose abundance often occur simultaneously at sites of inflammation. In monocytes and macrophages, glucose-oxygen deprivation stimulates the assembly of the NLRP3 inflammasome to generate the proinflammatory cytokine IL-1β. We found that concomitant glucose deprivation and hypoxia activated the NLRP3 inflammasome by constraining the function of HMG-CoA reductase (HMGCR), the rate-limiting enzyme of the mevalonate kinase pathway. HMGCR is involved in the synthesis of geranylgeranyl pyrophosphate (GGPP), which is required for the prenylation and lipid membrane integration of proteins. Under glucose-oxygen deprivation, GGPP synthesis was decreased, leading to reduced prenylation of the small GTPase Rac1, increased binding of nonprenylated Rac1 to the scaffolding protein IQGAP1, and enhanced activation of the NLRP3 inflammasome. In response to restricted oxygen and glucose supply, patient monocytes with a compromised mevalonate pathway due to mevalonate kinase deficiency or Muckle-Wells syndrome released more IL-1β than did control monocytes. Thus, reduced GGPP synthesis due to inhibition of HMGCR under glucose-oxygen deprivation results in proinflammatory innate responses, which are normally kept in check by the prenylation of Rac1. We suggest that this mechanism is also active in inflammatory autoimmune conditions.
CRIS-Team Scopus Importer:2024-07-26